肿瘤相关巨噬细胞通过诱导肝癌细胞自噬降低索拉菲尼的促凋亡作用 (Nan Fang Yi Ke Da Xue Xue Bao, 2019)
OBJECTIVE: To explore the molecular mechanism of sorafenib resistance in hepatoma cells and identify for new targets to reverse drug resistance. METHODS: THP-1 cells were induced into M2 tumor-associated macrophages (M2-TAMs) in vitro and identified by immunofluorescence. SMMC-7721 cells were co-cultured with M2-TAMs with or without sorafenib treatment. CCK-8 assay was used to observe the inhibitory effect of sorafenib on the cell proliferation. Annexin V/PI double staining and protein immunoblotting were used to assess the effect of sorafenib on the proliferation, apoptosis and the expressions of apoptosis-related proteins and autophagy-related protein in SMMC-7721 cells co-cultured with M2-TAMs in the presence or absence of the autophagy inhibitor chloroquine (CQ). RESULTS: The IC(50) of sorafenib at 48 h was 2.25 μmol/L in SMMC-7721 cells cultured alone, and increased to 4.72 μmol/L in the cells co-cultured with M2-TAMs. Compared with the cells cultured alone, the co-cultured SMMC-7721 cells showed significantly reduced apoptosis rate in response to sorafenib (P < 0.01) and significantly increased expression of Bcl-2 and Bcl-2/Bax ratio (P < 0.05) with also increased LC3-II/LC3-I ratio (P < 0.001) and lowered expression of p62 (P < 0.05), suggesting a significantly enhanced level of autophagy. CQ treatment significantly inhibited the proliferation of the co-cultured SMMC-7721 cells (P < 0.05), increased the cell apoptosis (P < 0.05) and reduced the Bcl-2/Bax ratio (P < 0.01). CONCLUSION: M2-TAMs can attenuate the inhibitory effect of sorafenib on the proliferation of hepatoma cells by increasing the level of autophagy, suggesting a new strategy for reversing sorafenib resistance induced by the tumor microenvironment by inhibiting autophagy.